PENERAPAN TEKNOLOGI WORDWALL DALAM PEMBELAJARAN DI SEKOLAH DASAR UNTUK MEWUJUDKAN TUJUAN KEEMPAT PROGRAM SDGS - Rafika Rahma Maulida; Trimurtini Trimurtini (Publikasi Inspirasi Indonesia, 2024)
This article aims to collect information about how elementary schools implement the Sustainable Development Goals (SDGs) program through the use of technology. The application of technology in learning is closely related to the realization of the fourth SDGs goal, namely Quality Education. Achieving quality education can be implemented through the application of wordwall-based technology in the learning process. Through the literature review method, some valid information was obtained regarding previous research that supports the application of technology in improving the quality of education. The positive impact of applying technology in the learning process is increasing students' motivation to learn, students' activeness, students' digital understanding and the formation of good morals. The realization of the fourth SDGs goal can also be interrelated with other SDGs goals.